Supplementation of Chlorella vulgaris meal in diet for growth performance of striped catfish juvenile Pangasianodon hypophthalmus - Nurhalimah Nurhalimah; Mas Bayu Syamsunarno; Mustahal Mustahal; Lukman Anugrah Agung (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2023)
The culture of striped catfish (Pangasianodon hypophthalmus) is overgrowing and facing the problem of relatively high feed prices. The feed prices affect feed grade; the cheaper the feed price, the lower the quality. This low feed quality may improve its quality by supplementing Chlorella vulgaris. Therefore, this study aimed to determine the level of supplementation of C. vulgaris meal in the feed that produces the best growth performance in striped catfish juveniles. A completely randomized design with three treatments and three replications was used in this experiment. The treatments were various levels of C. vulgaris, namely 0%, 1.5%, and 3%. C. vulgaris meal was added to the commercial feed (26-28% protein) according to the treatment with the coating method. The test feed was fed to striped catfish juveniles (6.66 ± 0.04 g in average weight) reared in an aquarium containing 55 L of water at a density of 20 juveniles, at satiation in the morning, afternoon, and evening for 50 days of the rearing period. Survival rate and hepatosomatic indices of the striped catfish were not affected by various supplementation levels of C. vulgaris meal (P>0.05), but the values of feed consumption, specific growth rate, feed conversion, and protein efficiency ratio of the striped catfish (P<0.05). Supplementation of 3.5% C. vulgaris meal in feed resulted in the best growth performance for striped catfish.